2012
DOI: 10.1371/journal.pone.0051048
|View full text |Cite
|
Sign up to set email alerts
|

Two Distinct Chronic Obstructive Pulmonary Disease (COPD) Phenotypes Are Associated with High Risk of Mortality

Abstract: RationaleIn COPD patients, mortality risk is influenced by age, severity of respiratory disease, and comorbidities. With an unbiased statistical approach we sought to identify clusters of COPD patients and to examine their mortality risk.MethodsStable COPD subjects (n = 527) were classified using hierarchical cluster analysis of clinical, functional and imaging data. The relevance of this classification was validated using prospective follow-up of mortality.ResultsThe most relevant patient classification was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
103
1
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(114 citation statements)
references
References 21 publications
7
103
1
3
Order By: Relevance
“…The high MetS prevalence in lower disease stages coincides with the reported high cardiovascular-related mortality in mild to moderate disease (5). Furthermore, recent studies have identified a so called "co-morbidity predominant subtype" of COPD patients, which is characterized by a cluster of metabolic co-morbidities, including obesity, CVD and T2DM (43,44). This seems to coincide with the most prevalent MetS components found in our review.…”
Section: Discussionsupporting
confidence: 86%
“…The high MetS prevalence in lower disease stages coincides with the reported high cardiovascular-related mortality in mild to moderate disease (5). Furthermore, recent studies have identified a so called "co-morbidity predominant subtype" of COPD patients, which is characterized by a cluster of metabolic co-morbidities, including obesity, CVD and T2DM (43,44). This seems to coincide with the most prevalent MetS components found in our review.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, systemic disease manifestations and acute exacerbations influence disease burden and mortality risk [1]. Extending the classical descriptions of the ''pink puffer'' and ''blue bloater'', recent unbiased statistical approaches [2,3] support the concept that body weight and body composition discriminate pulmonary phenotypes, and are predictors of outcome independent of lung function impairment. Incorporation of body composition into nutritional assessment has been a major step forward in understanding systemic COPD pathophysiology and nutritional potential.…”
Section: Scopementioning
confidence: 99%
“…In a cluster analysis of COPD patients age rather than disease severity accounted for most of the comorbidities [2]. One COPD phenotype is associated with cardiovascular and metabolic disease and is found in elderly patients [3]. A comprehensive analysis of comorbidities in COPD patients showed that almost all had at least one comorbidity and over 50% had four or more comorbidities [4].…”
Section: Introductionmentioning
confidence: 99%